2011
DOI: 10.1038/msb.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

Antisense expression increases gene expression variability and locus interdependency

Abstract: The function of non-coding antisense RNAs in yeast remains to be fully understood. Steinmetz and colleagues provide evidence for a general regulatory effect of antisense expression on sense genes and for a role in spreading regulatory signals between neighboring genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
176
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(194 citation statements)
references
References 35 publications
12
176
6
Order By: Relevance
“…In addition to biochemical diversity, a common theme for lncRNA function is temporal control of gene expression, regulating cellular programs that require highly specific and well timed responses to extracellular stimuli. [28][29][30] Unsurprisingly, misregulation of lncRNAs has been linked to the development of a multitude of human diseases including cancer 31 and heart failure. 32 The budding yeast Saccharomyces cerevisiae has been a robust system for genetic and molecular investigation of gene expression steps since its introduction as a model organism almost 30 y ago.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to biochemical diversity, a common theme for lncRNA function is temporal control of gene expression, regulating cellular programs that require highly specific and well timed responses to extracellular stimuli. [28][29][30] Unsurprisingly, misregulation of lncRNAs has been linked to the development of a multitude of human diseases including cancer 31 and heart failure. 32 The budding yeast Saccharomyces cerevisiae has been a robust system for genetic and molecular investigation of gene expression steps since its introduction as a model organism almost 30 y ago.…”
mentioning
confidence: 99%
“…104 Repression DCI1 Fatty acid metabolism YES GAL10 lncRNA 47,48,105 Repression GAL genes Galactose metabolism YES GAL10/GAL10s lncRNAs. 52,53 Promotes induction GAL genes Galactose metabolism YES KCS1 lncRNAs 106 Translational interference KCS1 Inositol hexa/hepta bisphosphate kinase YES SUT719 30,35 Repression SUR7 Plasma membrane protein YES CDC28 AS RNA 29 Promotes induction CDC28 Cell cycle regulator NO RTL. 107 Repression Ty1 Retrotransposon NO ICR1.…”
mentioning
confidence: 99%
“…Furthermore, lncRNAs are known to regulate expression of both proximal (cis) and distal (trans) protein-coding genes (Kornienko et al, 2013). In particular, antisense lncRNAs are involved in transcription regulation of protein-coding genes in cis (Wilusz et al, 2009;Xu et al, 2011). Our results suggest potential regulatory roles of the antisense lncRNA NONHSAG011351 on ERBB3 in human islets.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, using available genome-wide measurements of noise obtained by Newman et al 23 and plasticity by Tirosh and Barkai, 24 we have found that the level of antisense transcription across a gene is well correlated with both features (unpublished data). In support of this, Xu et al 25 also showed that genes with defined overlapping antisense transcripts showed a higher variation of gene expression across 5 different environmental conditions compared to those genes that did not. Another possibility is that antisense transcription might enforce the stochastic, 'burstier' mode of sense transcription that is characterized by infrequent, rapid bouts of transcription initiation, which can be observed as bright dots using RNA-FISH, and which is known to be inherently noisy.…”
Section: Roles For Dynamic Chromatinmentioning
confidence: 86%